BIBLIOMETRIC ANALYSIS OF RISK TOLERANCE: GLOBAL COLLABORATION AND THEMATIC EVOLUTION - Ayu Desi , Indrawati; Nyoman, Triaryati (STIE PGRI Dewantara Jombang, 2024)
This study aims to analyze the development of research on risk tolerance over the past two decades, focusing on collaborative networks among authors and countries, thematic evolution, and new research opportunities. The method used is bibliometric analysis based on R software and VOS Viewer. The research population includes 833 articles related to risk tolerance identified from the Scopus database. The study was conducted through network visualization, thematic clustering, and thematic evolution mapping. The results show that publications on risk tolerance have increased by 15% annually, with the United States as the primary contributor. The main recurring themes include risk assessment, decision-making, and financial risk tolerance. However, there is a gap in integrating the risk tolerance theme with broader concepts such as financial literacy. The analysis also indicates increased international collaboration, particularly in North America, Europe, and Asia, but with limited cooperation in Latin America and Africa. This study recommends further exploration of the relationship between risk tolerance, financial literacy, and technology-based decision-making. Additionally, it suggests enhancing cross-regional collaborations to broaden the scope and impact of research in this field.